Electromyographic analysis during exercises of ankle proprioception in unipodal support - Rodrigues, Eduardo Henrique Pereira (2017)
Introduction: Proprioception is a component of the somatosensory system that has the capacity to provide information afferent to the Central Nervous System about the position and movement of the segments of several receptors. Objective: To analyze the electromyographic activity of muscles, tibialis anterior, fibular, important in the stabilization of the ankle, multifidus and transverse muscles of the abdomen, important in stabilizing the lumbar spine during proprioception exercises. Methods: Participants answered a questionnaire about their personal and anthropometric data and performed proprioceptive exercises in unipodal support in different proprioception devices. Results: The balance plate was the equipment with the highest values   of peak contraction. The tibialis anterior, multifidus and fibular muscles presented the most significant differences for the male and female groups. Conclusions: Of the muscles evaluated by electromyography the ones that presented the most significant differences were the anterior tibial, multifidus and the fibular ones.